I-Measurement of Some Elastic Properties of a Solid Material Made by Consolidated Nanosized Particles of Zinc Compounds at Different Temperatures. II- Particle Size Meaq,rement by TEM - Ahmad, S. Shakeel; Mahmood, Khursheed; Hussain, Altaf; Karim, Arif (Biological Sciences - PJSIR, 2007)
The elastic properti es of a sol id made by consolidated nano particles of two zinc compounds were evaluated at different temperatures (from 303 °K to 343 °K). The n ano particle s were prepared chemically. For studying the elastic properties of the solid and speed of sound within the material , two samples were prepared. Use of ultrasonic reverbersion technique for measuring the tran sit time and the wave velocity in the solid placed in oil and the effect of l ongitudinal and shear waves on th e sampl e are discussed. The arrival times of individual reverbersions were compared for the estimation of compressional and shear velocities. The compressional, shear and the bulk modulus, were calculated in both th e samples. In one pellet, without appli cation of pressure on the material , some porosity was observed reducin g th e calculated parameters. It was concl uded that the presence of cracks, twining and grain boundari es within the bulk material can alter the ultrasonic velocity as well as the elastic properties. The effect of hydrostatic pressure on the solid disk was also studied. For particl e size measurements, the size distribut ion curve was drawn using the method of cryo-transmis sion electron microscopy (cryo-TEM) image analysis throu gh dynamic light scattering (DLS) technique. A hi stogram has been constructed showing size distribution of particl es di spersed in the medium. The sizes (weight average diameter) were recorded between 21 -1 00 nm . The results of such particle size measurements show that th e dynamic light scattering and acoustic micro imaging techniques, both are nondestructive and allow characterization of a l arge number of particl es more rapidly. By assembling nano sized particles, the prescribed properties of the material can be altered.